Flutuação sazonal de B/CYDV e características biológicas de isolados de BYDV-PAV - Parizoto, Gabriela (2011)
The viral disease known as yellow dwarf disease, caused by species of Barley yellow dwarf virus - BYDV and Cereal yellow dwarf virus - CYDV is considered the most frequent and economically significant virus of winter cereal crops, reducing production throughout the world. Species of BYDV and of CYDV are transmitted by diverse species of aphids (Hemiptera, Aphididae) and they are capable of infecting more than 150 species of plants within the Poaceae family. Among the species of BYDV and CYDV, BYDV-PAV predominates in most of the producing regions of the world, including the Brazilian wheat growing regions. Therefore, the objective of this study was to obtain frequency data of the viral and vector populations in the field and to analyze biological attributes that may influence the population dynamic. Monitoring of the temporal fluctuation of the population of B/CYDV species was performed through weekly collections of vector aphids in the period from 01/2009 to 07/2010 and collections every two weeks of plants with symptoms in the period from 07/2009 to 08/2010 in corn (summer), and wheat and oats (winter) plots in Coxilha-RS. The aphids were collected at random and individually transferred to oat or wheat plants (in accordance with the host of origin) where they remained for 10 days for transmission. After 30 days, the plants were evaluated in regard to the presence of symptoms and viral identification through DAS-ELISA. The same serological test was applied to plants collected in the field. So as to determine biological characteristics that may have a direct effect on viral fluctuation, the capacity of 35 BYDV-PAV isolates, obtained in the Brazilian producing regions (population 2007/2009), for infecting two hosts (Triticum aestivum L. and Avena strigosa Schreb) and the efficiency of transmission by aphid vectors (Rhopalosiphum padi, Sitobion avenae, Schizaphis graminum, Metopolophiun dirhodum and Sipha maydis) were evaluated. Twenty plants for each combination isolate x host plant x vector were inoculated, using three aphids per plant (acquisition of 48h; transmission of 72h). The positive diagnosis of transmission and infection were performed by evaluation of symptoms 15, 30 and 45 days after transmission and by DAS-ELISA (30 days). Of the 739 aphids collected, 12,7% transmitted B/CYDV, such that of this total R. padi constituted 92,5% and S. avenae 7,5 %. Of the viral species transmitted by R. padi, 97,7% were BYDV-PAV, 2.3% CYDV-RPV and 2.3% BYDV-MAV in mixed infection with BYDV-PAV. Individuals of the species S. avenae collected transmitted only BYDV-PAV. Of the 625 plant samples collected, 65,8% were infected with BYDV-PAV (oats and wheat) and 0,48% with BYDV-MAV (oats) in mixed infection with BYDV-PAV. Both in sampling of plants and aphids, BYDV-PAV was the predominant species, being detected in oats and wheat and in the vectors R. padi and S. avenae. All the isolates were transmitted by R. padi (94,3%), followed by S. avenae (76,1%) and M. dirhodum (63,4%). None of the isolates were transmitted by S. graminum and S. maydis. All the isolates were capable of infecting oats and wheat. The high transmission efficiency by three species of aphids (from beginning and end of the wheat crop cycle) and the pathogenicity to wheat and oats are attributes that may contribute to the prevalence of BYDV-PAV